2016
DOI: 10.1039/c6dt03776c
|View full text |Cite
|
Sign up to set email alerts
|

A simultaneous disulfide bond cleavage, N,S-bialkylation/N-protonation and self-assembly reaction: syntheses, structures and properties of two hybrid iodoargentates with thiazolyl-based heterocycles

Abstract: Solvothermal reactions of AgI with the vulcanization accelerator 2,2'-dibenzothiazolyl disulfide and hydroiodic acid in alcohols afford two hybrid iodoargentates with one-dimensional structures, namely (Etmbt)[AgI] (1, Hmbt = 2-mercaptobenzothiazole) and {(Hmbt)[AgI]} (2). The syntheses of both 1 and 2 involve unprecedented multiple in situ reactions. Specifically, a simultaneous disulfide bond cleavage, N and S donor atoms bialkylation, and self-assembly reaction lead to 1 that contains a discrete N,S-biethyl… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

0
5
0

Year Published

2017
2017
2023
2023

Publication Types

Select...
10

Relationship

3
7

Authors

Journals

citations
Cited by 17 publications
(5 citation statements)
references
References 113 publications
0
5
0
Order By: Relevance
“…Each EBT ligand was formed from an HBT molecule via in situ reactions. As shown in Scheme S1, the N-alkylation reaction introduces an ethyl on the thiazole N atom; meanwhile, the sulfhydryl group was deprotonated and further coordinates to the neutral [Cu 4 I 4 ] core via forming a Cu–S bond. , The Cu–I and Cu–S bond distances are in their normal ranges of 2.517(1)–2.785(1) Å and 2.234(1)–2.354(1) Å, respectively . The Cu1···Cu2′ distance of 2.684(1) Å is shorter than the sum of the van der Waals radii of Cu, suggesting there are Cu···Cu interactions in UJN-Cu .…”
Section: Resultsmentioning
confidence: 99%
“…Each EBT ligand was formed from an HBT molecule via in situ reactions. As shown in Scheme S1, the N-alkylation reaction introduces an ethyl on the thiazole N atom; meanwhile, the sulfhydryl group was deprotonated and further coordinates to the neutral [Cu 4 I 4 ] core via forming a Cu–S bond. , The Cu–I and Cu–S bond distances are in their normal ranges of 2.517(1)–2.785(1) Å and 2.234(1)–2.354(1) Å, respectively . The Cu1···Cu2′ distance of 2.684(1) Å is shorter than the sum of the van der Waals radii of Cu, suggesting there are Cu···Cu interactions in UJN-Cu .…”
Section: Resultsmentioning
confidence: 99%
“…In recent years, a large number of organic cation-directed hybrid metal halogenide materials have received a great deal of attention because of their distinctive photoelectric properties. It is found that the template or structure-directing agent (SDA) occupies a very significant position in the crystal structure construction and band structure decorating as well as photoelectric property regulation of hybrid metal halogenide materials . These surprising discoveries incite us to explore new types of stable visible light-driven photocatalysts via the introduction of conjugated organic cations as photosensitive templates and electron acceptors into binary CuX or AgX based on the idea of electronic band structural decoration.…”
Section: Introductionmentioning
confidence: 99%
“…The (SbI 4 ) − anionic chain adopts a zigzag fashion that is formed by adjacent (SbI 6 ) octahedra each sharing two nonadjacent edges. The organic moieties in the molecular structure are mono-protonated for charge balance requirement, , which pack equimolarly with their oppositely oriented cations in the crystal lattice (Figure c). The nearest centroid-to-centroid distance between two neighboring 3ppi cations is 3.866 (1) Å, being slightly longer than 3.8 Å, which indicates there are no significant π···π packing interactions within the organic counterions.…”
Section: Resultsmentioning
confidence: 99%